2021
DOI: 10.1136/tsaco-2021-000736
|View full text |Cite
|
Sign up to set email alerts
|

Driving under the influence: a multi-center evaluation of vehicular crashes in the era of cannabis legalization

Abstract: BackgroundEleven states have instituted laws allowing recreational cannabis use leading to growing public health concerns surrounding the effects of cannabis intoxication on driving safety. We hypothesized that after the 2016 legalization of cannabis in California, the use among vehicular injury patients would increase and be associated with increased injury severity.MethodsSan Diego County’s five adult trauma center registries in were queried from January 2010 to June 2018 for motor vehicle or motorcycle cras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
(23 reference statements)
0
13
1
Order By: Relevance
“…Previously reported averages among 10 injured ED patients in U.S. hospitals (15% by biosample, 19.7% by self‐report) are generally lower than what we discovered in our study, although we did not conduct a formal comparison 11 . Using content that includes different types of consumption will allow research studies to characterize use patterns accurately.…”
Section: Discussioncontrasting
confidence: 80%
“…Previously reported averages among 10 injured ED patients in U.S. hospitals (15% by biosample, 19.7% by self‐report) are generally lower than what we discovered in our study, although we did not conduct a formal comparison 11 . Using content that includes different types of consumption will allow research studies to characterize use patterns accurately.…”
Section: Discussioncontrasting
confidence: 80%
“…94,95 Further, a California-based study examining THC toxicology screens in motor vehicle accident patients, did find a significant increase in positive screens, but this increase was not associated with implementation of RCL. 96 However, three studies suggest a negative impact of RCL, as one U.S. study found both RCL states and their neighboring states had an increase in motor vehicle fatalities immediately following RCL. 97 Additionally, a Canadian study did find a significant increase in moderately injured drivers with cannabis positive blood screens post-RCL.…”
Section: Driving-related Outcomesmentioning
confidence: 99%
“…Of the 29 articles included in this review, eight focused on the legalization of medical cannabis [22][23][24][25][26][27][28][29], with respect to recreational cannabis, there were 13 papers that addressed the impact of its legalization with respect to traffic accidents [3,[30][31][32][33][34][35][36][37][38][39][40][41], two papers included both medical and recreational cannabis [42,43], and seven papers discussed the decriminalization and legalization of cannabis in general [8,[43][44][45][46][47][48].…”
Section: Characteristics Of the Studies Included In The Systematic Re...mentioning
confidence: 99%
“…With regard to the samples, it should be noted that these were mainly made up of men, except for two studies with a greater presence of women [3,23], with a minimum age of 14 years [26,48]. Among the selected papers were a large number of studies that, in addition to collecting data on cannabis use, also reported on alcohol use [3,8,[22][23][24][25]28,29,36,37,[44][45][46].…”
Section: Characteristics Of the Studies Included In The Systematic Re...mentioning
confidence: 99%
See 1 more Smart Citation